(untitled) (Journal of Economic Research & Business Administration, 2017)
The problem of improving the efficiency and competitiveness of Kazakhstan’s economy is largely connected with the innovative development of national economy. In turn, innovative development of the economy requires the use of progressive forms of organization of activities of business entities. In this aspect, the problem of formation and development of cluster forms of organization of production in Kazakhstan is of particular relevance. Research of processes of cluster development of Kazakhstan’s economy shows that for 2004-2016 years in the country, a positive trend in the field of formation and development of clusters in various sectors of the economy. However, due to a number of internal and external factors of cluster development, the country still has not received its development. In this article conducted systematization of the processes of cluster development of Kazakhstan’s economy. The study identified 3 stages of formation and development of clusters in the system of national economy. On this basis reveals the specific features and development trends of clusters in the conditions of transition to industrial – innovative development of the economy; the formation of cluster models with respect to the centers of economic growth; the development of promising and innovative clusters in various sectors of the economy. Generally considered positive trends and disadvantages of cluster development in Kazakhstan and, accordingly, recommendations for further improvement of processes of cluster development in the Republic.